Chromosome‐level reference genome assembly provides insights into aroma biosynthesis in passion fruit (Passiflora edulis). (28th December 2020) - Ma, Dongna; Dong, Shanshan; Zhang, Shengcheng; Wei, Xiuqing; Xie, Qingjun; Ding, Qiansu; Xia, Rui; Zhang, Xingtan
Abstract: Passion fruit, native to tropical America, is an agriculturally, economically and ornamentally important fruit plant that is well known for its acid pulp, rich aroma and distinctive flavour. Here, we present a chromosome‐level genome assembly of passion fruit by incorporating PacBio long HiFi reads and Hi‐C technology. The assembled reference genome is 1.28 Gb size with a scaffold N50 of 126.4 Mb and 99.22% sequences anchored onto nine pseudochromosomes. This genome is highly repetitive, accounting for 86.61% of the assembled genome. A total of 39, 309 protein‐coding genes were predicted with 93.48% of those being functionally annotated in the public databases. Genome evolution analysis revealed a core eudicot‐common γ whole‐genome triplication event and a more recent whole‐genome duplication event, possibly contributing to the expansion of certain gene families. The 33 rapidly expanded gene families were significantly enriched in the pathways of isoflavone biosynthesis, galactose metabolism, diterpene biosynthesis and fatty acid metabolism, which might be responsible for the formation of featured flavours in the passion fruit. Transcriptome analysis revealed that genes related to ester and ethylene biosynthesis were significantly upregulated in the mature fruit and the expression levels of those genes were consistent with the accumulation of volatile lipid compounds. The passion fruit genome analysis improves our understanding of the genome evolution of this species and sheds new lights into the molecular mechanism of aroma biosynthesis in passion fruit.